Maternal depression and malnutrition in children in southwest Uganda: a case control study - Ashaba, Scholastic; Rukundo, Godfrey Zari; Beinempaka, Florence; Ntaro, Moses; LeBlanc, John C. (BMC Public Health, 2015)
Background: Malnutrition remains one of the most significant child health problems in developing countries with an estimated 53 % of child deaths per year attributed to being underweight. The 2011 Uganda Demographic and Health Survey (UDHS) showed that 38 % of the children were stunted and 16 % were underweight. While dietary and environmental factors are known major contributors to children's nutritional status, maternal depression may also contribute since it disrupts the mothers’ ability to cope with demands of childcare. This study aimed to determine the association between maternal depression and malnutrition in children aged one to 5 years in southwest Uganda. Methods: The study was undertaken between October and December 2014 on children aged one to 5 admitted to the Mbarara regional referral hospital. Cases were malnourished children and controls were children with other chronic conditions but normal nutritional status admitted to the same hospital. Children’s ages were recorded, weight and height taken and converted into height for age, weight for height and weight for age and malnutrition determined based on WHO child growth standards. Mothers of both groups of children were assessed for depression using the depression module of the Mini International Neuropsychiatric Interview (MINI). Participants provided informed consent prior to enrollment. The study was approved by Mbarara University of Science and Technology Research Ethics Committee and funded by Micro Research. Results: All 166 mothers who were approached agreed to participate in the study. The prevalence of depression among mothers of malnourished children (86 cases) was 42 % compared to 12 % among mothers of controls (86 controls). The mean age was 25 years (SD 4.43, range 18–40 years). The majority (75 %) were married and most were peasant farmers (62 %). Maternal depression was significantly associated with malnutrition in children with a crude odds ratio of 2.23 (1.08–1.89) and an adjusted odds ratio of 2.4 (1.11–5.18). Conclusion: Maternal depression impacts negatively on child nutrition and development as shown by a higher prevalence of depression among mothers of malnourished children compared to the control group. Routine screening and treatment for depression should be included in all maternal and child health clinics.
Keywords: Maternal depression; Malnutrition; Children under five years